2023
DOI: 10.1021/acsagscitech.3c00072
|View full text |Cite
|
Sign up to set email alerts
|

Effective Electrochemical Synthesis of an Important Fungicide Tetramethylthiuram Disulfide and Its Bioactive Analogues

Olga M. Mulina,
Evgeniya D. Bokova,
Mikhail M. Doronin
et al.

Abstract: Tetramethylthiuram disulfide (TMTD, thiram) is one of the most important fungicides and is widely used in agriculture for seed treatment and crop protection. TMTD is produced by a number of plants. Its annual sales are estimated at tens of millions of US dollars. Traditional chemical synthesis of thiram is accompanied by the formation of a significant amount of waste, including inorganic salts, thioacids, polysulfides, etc. Herein, we report an advanced method of TMTD and its structural analogues production, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…In 2023, Terent'ev and co-workers utilised a combination of amines and carbon disulphide under constant current conditions in an undivided electrochemical cell for the synthesis of thiram and its analogues (Scheme 22a). 88 Potassium iodide played dual roles as a redox active catalyst and an electrolyte. As proposed, mechanistic studies suggested that a hydroxide anion formed at the cathode and assisted the formation of di-thiocarbamate via nucleophilic attack of 162 on CS 2 .…”
Section: Electrochemical Strategies For Drug Synthesismentioning
confidence: 99%
“…In 2023, Terent'ev and co-workers utilised a combination of amines and carbon disulphide under constant current conditions in an undivided electrochemical cell for the synthesis of thiram and its analogues (Scheme 22a). 88 Potassium iodide played dual roles as a redox active catalyst and an electrolyte. As proposed, mechanistic studies suggested that a hydroxide anion formed at the cathode and assisted the formation of di-thiocarbamate via nucleophilic attack of 162 on CS 2 .…”
Section: Electrochemical Strategies For Drug Synthesismentioning
confidence: 99%